ASSESSMENT OF THE STRUCTURES AND INTERRELATION OF RISK FACTORS PREDISPOSING TO MYOCARDIAL INFARCTION IN YOUNG PEOPLE - Khasanjanova F.O; Abdushukurova K.R (Scholar Express Journals, 2024)
In this paper, we studied the structure and relationship of risk factors predisposing to myocardial infarction in young people and assess their significance. This study was conducted on the basis of the Samarkand regional branch of the Republican Specialized Scientific and Practical Medical Center of Cardiology (SRF RSNPMC). The study included a retrospective analysis of 108 medical records of patients under the age of 45 years hospitalized in the departments of acute coronary syndrome (ACS) and coronary artery disease (CHD). All patients, depending on the clinical diagnosis, were divided into 2 groups. 72% of patients had a large–focal infarction, 28% had a small-focal one
Keywords: Atrial fibrillation; arterial hypertension; left atrium; right atrium; ECG